Comparison between articular chondrocytes and mesenchymal stromal cells for the production of articular cartilage implants - Frerker, Nadine; Karlsen, Tommy A.; Stensland, Maria; Nyman, Tuula A.; Rayner, Simon; Brinchmann, Jan E. (Frontiers in Bioengineering and Biotechnology, 2023)
Focal lesions of articular cartilage give rise to pain and reduced joint function and may, if left untreated, lead to osteoarthritis. Implantation of in vitro generated, scaffold-free autologous cartilage discs may represent the best treatment option. Here we compare articular chondrocytes (ACs) and bone marrow-derived mesenchymal stromal cells (MSCs) for their ability to make scaffold-free cartilage discs. ACs produced more extracellular matrix per seeded cell than MSCs. Quantitative proteomics analysis showed that AC discs contained more articular cartilage proteins, while MSC discs had more proteins associated with cartilage hypertrophy and bone formation. Sequencing analysis revealed more microRNAs associated with normal cartilage in AC discs, and target predictions suggested that differential expression of microRNAs in the two disc types were important mechanisms behind differential synthesis of proteins. We conclude that ACs should be preferred over MSCs for tissue engineering of articular cartilage.